A flexible wearable strain sensor for human-motion detection and a human–machine interface. Issue 41 (4th October 2022) - Zhang, Hao; Zhang, Dongzhi; Guan, Jingrun; Wang, Dongyue; Tang, Mingcong; Ma, Yanhua; Xia, Hui
Abstract : Electronic skin arrays and smart gloves are designed based on AgNFs/MWCNTs flexible strain sensors to realize motion monitoring and human–computer interactions. Abstract : With the development of Internet-of-Things (IoT) technology and fifth-generation mobile communications technology (5G), the demand for smart wearable devices is increasing. Therefore, strain sensors with high stretchability have been developed rapidly. The realization of electronic skin and smart wearable products requires continuous breakthroughs in flexible strain sensors. Here, a flexible, stretchable sensor with a sandwich structure was fabricated using two layers of polydimethylsiloxane (PDMS) and one sensing layer. The highly conductive sensing layer consisted of silver nanoflowers (AgNFs) and multi-walled carbon nanotubes (MWCNTs), whose synergistic effect successfully improved the flexibility and conductivity of the films. The sensor has high scalability (100%), a fast response time (60 ms), a high gauge factor (1187.07), and high stability, enabling the detection of physiological and motion signals such as the pulse, speech recognition, and the positions of joints. An electronic skin array was fabricated based on sensor-array technology to realize the multi-point-distributed detection of skin surface pressure. Moreover, a smart glove was designed using this electronic skin, and hand-gesture tracking was realized using a virtual-display interface through wireless transmission and 3D modeling technology. The sensor has broad development prospects in the fields of human–computer interactions, mechanical control and wearable electronic devices.